2018
DOI: 10.1038/s41598-018-25448-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a fumarolic system inferred from a multiphysics approach

Abstract: Fumaroles are a common manifestation of volcanic activity that are associated with large emissions of gases into the atmosphere. These gases originate from the magma, and they can provide indirect and unique insights into magmatic processes. Therefore, they are extensively used to monitor and forecast eruptive activity. During their ascent, the magmatic gases interact with the rock and hydrothermal fluids, which modify their geochemical compositions. These interactions can complicate our understanding of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Geochemistry, Geophysics, Geosystems Similar signals, recorded at Old Faithful geyser in Yellowstone National Park (USA), have been analyzed by Kedar et al (1996), who found the harmonic motion to be caused by elastic waves reverberating in a solid medium such as a near-surface soft layer. Applying the Kedar formula f = Vs/4h to our data with f = 10 Hz and Vs = 200 m/s (Bruno et al, 2007), it gives us the result of h = 5 m. This estimate is consistent with the results reported in the literature for the hydrothermal areas of Solfatara and Pisciarelli (Amoroso et al, 2018;Bruno et al, 2007;De Landro et al, 2017;Di Giuseppe & Troiano, 2019;Gresse et al, 2018). The study of the fumarolic tremor source mechanism is important to define quantitative relationships between the generation of the seismic signal and the dynamics of hydrothermal fluids (gas and bubbling mud) at Pisciarelli.…”
Section: 1029/2019gc008610supporting
confidence: 90%
“…Geochemistry, Geophysics, Geosystems Similar signals, recorded at Old Faithful geyser in Yellowstone National Park (USA), have been analyzed by Kedar et al (1996), who found the harmonic motion to be caused by elastic waves reverberating in a solid medium such as a near-surface soft layer. Applying the Kedar formula f = Vs/4h to our data with f = 10 Hz and Vs = 200 m/s (Bruno et al, 2007), it gives us the result of h = 5 m. This estimate is consistent with the results reported in the literature for the hydrothermal areas of Solfatara and Pisciarelli (Amoroso et al, 2018;Bruno et al, 2007;De Landro et al, 2017;Di Giuseppe & Troiano, 2019;Gresse et al, 2018). The study of the fumarolic tremor source mechanism is important to define quantitative relationships between the generation of the seismic signal and the dynamics of hydrothermal fluids (gas and bubbling mud) at Pisciarelli.…”
Section: 1029/2019gc008610supporting
confidence: 90%
“…Our study builds upon previous geophysical studies that imaged subsurface structures, fluid flow pathways, and hydrothermal alteration in volcano‐hydrothermal systems (e.g., Aizawa et al, ; Bouligand et al, ; Byrdina et al, ; Finn et al, ; Finn & Morgan, ; Gresse et al, , ; Hase et al, ; Pasquet et al, ; Revil et al, ; Rosas‐Carbajal et al, ; Soengkono, ). In contrast to many of these studies that used a single geophysical method and often resulted in a nonunique interpretation, we combine several different geophysical methods and quantify the spatial relationships among the diverse data sets.…”
Section: Introductionmentioning
confidence: 65%
“…At the Solfatara we do not expect a prevalently 1D propagation medium (De Landro et al, 2017;Gresse et al, 2018). Indeed, the scattered waves are both associated with the presence of scatterers in the media as well as with 2D/3D structural effects.…”
Section: Scattering Mean Free Path Estimationmentioning
confidence: 73%
“…Finally, 3D analysis of P (De Landro et al, 2017 and surface waves (Serra et al, 2016), and inspection of 2D profiles (Bruno et al, 2017;Gammaldi et al, 2018) pointed out a separation of the central part of the crater in two domains, with the NE sector having higher velocities than the SW one. As suggested by geoelectric measurements (Byrdina et al, 2014;Gresse et al, 2018), which are more sensitive to the presence of liquid/gas phases, this separation can be ascribed to a different concentration of water, which is more abundant in the SW domain. At larger depths several nearvertical normal faults individuated in the reflection profiles likely represent the pathways for ascending gas.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation